Novel near-neutral zinc ion battery as well as electrolyte and preparation method thereof
By using a new near-neutral zinc ion battery electrolyte in an aqueous zinc ion battery, the electrolyte consists of zinc salt electrolyte and anionic surfactant, the dendrite growth and corrosion of zinc electrodes are solved, and the battery performance with high cycle stability and long life is achieved.
Patent Information
- Application Number
- CN202311137890.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-04
- Publication Date
- 2025-03-04
AI Technical Summary
The existing aqueous zinc ion batteries have problems such as dendrites growth, corrosion, and hydrogen evolution of metal zinc negative electrodes, which limit the stability and reversibility of the battery.
A new type of near-neutral zinc ion battery electrolyte is used, which consists of zinc salt electrolyte and anionic surfactant, which can improve the adsorption and electrodeposition behavior of the electrode surface and inhibit the corrosion of zinc electrodes and dendrite growth.
The high cycle stability of metal zinc negative electrode is achieved, dendrite and corrosion problems are avoided, the battery life and coulomb efficiency are improved, and it is easy to prepare and low cost.
Smart Images

Figure HDA0004432482560000011 
Figure HDA0004432482560000012 
Figure HDA0004432482560000021
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of battery energy storage, and specifically relates to a novel near-neutral zinc ion battery electrolyte which can realize reversible deposition / stripping of zinc electrodes, inhibit corrosion, hydrogen evolution, and dendrite growth of zinc electrodes, and has low surface tension and improves electrode surface adsorption. Background Art
[0002] In recent years, the global economy has grown rapidly, and the demand for energy has also increased. The large-scale use of traditional fossil energy has brought about serious pollution problems. At the same time, due to the non-renewable nature of traditional fossil energy, the price of fossil energy continues to rise. Under the goals of carbon peak and carbon neutrality, it is urgent to increase the utilization of clean energy and improve the energy structure. However, traditional renewable clean energy such as wind energy, solar energy, and tidal energy have temporal and spatial discontinuities and require energy storage batteries for regulation. Therefore, new secondary batteries with high safety, high reversibility, and high specific energy have a great role in alleviating the current energy pressure and achieving the dual carbon goals.
[0003] Currently, the more mature secondary batteries include lead-acid batteries and lithium-ion batteries. Among them, lead-acid batteries are low in cost, high in voltage (2.0V), and safe, and are widely used in storage batteries. However, due to the pollution problem of lead and the large mass of the electrodes, their energy density is low, their life is short, and they are relatively bulky, making it difficult for lead-acid batteries to meet people's demand for high-performance batteries. Compared with lead-acid batteries, lithium-ion batteries have high energy density, light size, and high reversibility. They are a new generation of high-performance secondary batteries. However, due to resource limitations, lithium-ion batteries are relatively expensive. At the same time, during the circulation process of lithium-ion batteries, there is a problem of dendrite growth leading to short circuits. In addition, the use of flammable organic electrolytes makes lithium-ion batteries less safe and prone to fire, making them unsuitable for large-scale energy storage.
[0004] Compared to lithium, zinc reserves on Earth are extremely large, and China's zinc reserves rank first in the world. Aqueous zinc-based batteries use aqueous electrolytes, which are extremely safe. At the same time, their high reversibility, low cost, and high specific energy make them have great energy storage prospects and are expected to become a new generation of secondary batteries for energy storage.
[0005] However, due to the poor thermodynamic stability of zinc metal in aqueous electrolytes, there are problems such as corrosion, hydrogen evolution, and dendrite growth during the electrical cycle, which limits the further development of batteries. Therefore, it is crucial to develop high-performance aqueous zinc-based batteries, improve the stability and reversibility of metal zinc negative electrodes, and eliminate the inherent defects of traditional zinc negative electrodes. Summary of the invention
[0006] The purpose of the present invention is to solve the complex problems of dendrite growth, corrosion, hydrogen evolution, etc. of the metal zinc negative electrode of the existing aqueous zinc ion battery. A new near-neutral zinc ion battery electrolyte is provided to eliminate the side reactions of the metal zinc negative electrode in the zinc salt electrolyte and the problem of poor reversibility.
[0007] The invention discloses a novel electrolyte of a near-neutral zinc ion battery of anionic surfactant type. The electrolyte is mainly composed of zinc salt electrolyte, which can maintain normal redox behavior of zinc electrode. The additive is anionic surfactant, which has amphiphilicity, including strong hydrophobic group (lipophilic) and ionic group (hydrophilic), which can improve adsorption and electrodeposition behavior of electrode surface.
[0008] One of the purposes of the present invention is to provide a zinc ion battery using a novel anionic surfactant electrolyte, wherein the negative electrode is metallic zinc (zinc foil, zinc powder, zinc alloy, etc.), and the positive electrode is vanadium-based oxides (vanadium trioxide, vanadium pentoxide, vanadium trioxide, vanadium dioxide and its corresponding ion intercalation compounds), manganese-based oxides, Prussian blue analogs, and organic compounds such as polyaniline. The electrolyte uses a novel anionic surfactant electrolyte. Another purpose of the present invention is to provide a method for preparing the novel anionic surfactant electrolyte, which comprises the following steps:
[0009] (1) Weighing zinc salt powder by mass, adding deionized water, stirring and dissolving, to obtain a zinc salt electrolyte solution (0.2M-3M);
[0010] (2) introducing nitrogen into the zinc salt electrolyte solution obtained in step (1) and ultrasonicating it for 30 minutes to uniformly disperse it and remove dissolved oxygen in the electrolyte solution;
[0011] (3) Weigh the corresponding mass of anionic surfactant electrolyte additive (0.01 g L -1 -10g L -1 ), added to the zinc salt electrolyte obtained in step (2) to obtain a zinc salt electrolyte solution containing anionic surfactant, wherein the additive content is 0.01 g L -1 -10g L -1 ;
[0012] (4) nitrogen is introduced into the zinc salt electrolyte solution containing anionic surfactant obtained in step (3) and ultrasonicated for 30 minutes to make it uniformly dispersed and remove dissolved oxygen in the electrolyte, thereby obtaining a new electrolyte containing anionic surfactant for zinc ion battery.
[0013] Furthermore, in the above technical solution, the zinc salt electrolyte includes zinc sulfate, zinc trifluoromethanesulfonate, zinc chloride, zinc acetate, zinc nitrate, zinc perchlorate, zinc nitrate, zinc tetrafluoroborate and other zinc salts, which can be a single compound or a mixture of different zinc salts. The anionic surfactant electrolyte additive includes alkyl sulfate, alkyl sulfonate, alkylbenzene sulfonate and the like, which can be a single anionic surfactant or a mixture of multiple anionic surfactants. The methods include stirring and ultrasound, and the deoxygenation method includes nitrogen and argon.
[0014] Furthermore, in the above technical solution, the concentration of the zinc salt is 0.2M-3M, and the concentration of the anionic surfactant additive is 0.01g L -1 -10g L -1 ; preferably 2M zinc salt electrolyte, 0.1g L -1 Anionic surfactant additive.
[0015] Furthermore, in the above technical solution, the alkyl group in the alkyl sulfate, alkyl sulfonate, and alkylbenzene sulfonate is a straight-chain or branched alkane with a carbon number of 6 to 18.
[0016] The novel anionic surfactant electrolyte proposed by the present invention has a main electrolyte of zinc salt (zinc sulfate, zinc trifluoromethanesulfonate, zinc chloride, zinc acetate, zinc nitrate, zinc perchlorate, zinc nitrate, zinc tetrafluoroborate, etc.). The zinc ion battery composed of the novel anionic surfactant electrolyte has a negative electrode side of metallic zinc (zinc sheet, zinc powder, zinc foam, zinc copper alloy, zinc tin alloy), and a positive electrode of vanadium-based oxides (such as vanadium trioxide, vanadium pentoxide, vanadium trioxide, vanadium dioxide and its corresponding ion intercalation compounds), manganese-based oxides, Prussian blue analogs, and organic compounds such as polyaniline. Metallic zinc can achieve extremely high cycle stability in the novel anionic surfactant electrolyte, and realize dendrite-free and corrosion-free cycles. At the same time, the novel anionic surfactant electrolyte has the advantages of easy preparation and low cost, and can be used on a large scale.
[0017] (1) The anionic surfactant electrolyte prepared by the present invention can utilize the hydrophobic group of the surfactant to promote the desolvation of zinc ions, accelerate the electrode reaction kinetics, and inhibit the corrosion of the zinc electrode by active water.
[0018] (2) The anionic surfactant electrolyte proposed in the present invention can utilize the hydrophilic anionic groups to improve the adsorption of zinc ions on the electrode surface, enhance the two-dimensional diffusion, and achieve dendrite-free deposition on the zinc electrode surface.
[0019] (3) The novel anionic surfactant electrolyte proposed in the present invention can realize a cycle without side reactions, thereby improving the battery life and coulombic efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 is a representative molecular formula of anionic surfactants used; wherein (a) sodium dodecyl sulfate; (b) sodium dodecylbenzene sulfonate; (c) sodium dodecyl sulfonate;
[0021] Figure 2 (a) is the deposition morphology of the reference example; (b) is the symmetric battery performance of the reference example;
[0022] Figure 3 Deposition morphologies of different embodiments of the novel anionic surfactant electrolyte, wherein a to f correspond to embodiments 1 to 6 in sequence;
[0023] Figure 4 The symmetrical battery performance diagram of Examples 1-6, wherein a to f correspond to Examples 1-6 in sequence;
[0024] Figure 5 (a) is a deposition morphology diagram of comparative example 1; (b) is a symmetric battery performance diagram of comparative example 1;
[0025] Figure 6 (a) is the deposition morphology diagram of comparative example 2; (b) is the symmetrical battery performance diagram of comparative example 2. DETAILED DESCRIPTION
[0026] The present invention will be further described in the following examples, but the present invention is not limited thereto.
[0027] In the following reference examples, embodiments and comparative examples, the conventional zinc symmetrical battery is assembled as follows: in a CR2032 button cell, metal zinc is used as an electrode, glass fiber is used as a separator, and 100 microliters of electrolyte is added.
[0028] Reference example
[0029] Zinc salt electrolyte without anionic surfactant: Weigh 0.58g ZnSO4·7H2O, add 1mL deionized water, stir to fully dissolve, and pass nitrogen to deoxygenate for 30min. Using the prepared zinc salt electrolyte, zinc sheets were used as electrodes to assemble a traditional zinc symmetric battery and test it. At 2mA cm -2 At a current density of 1 mAh cm -2 At a cycle depth of Figure 2 a, lifespan is about 50h ( Figure 2 b).
[0030] Example 1
[0031] The electrolyte comprises: ZnSO4 as electrolyte, sodium dodecyl sulfate as additive anionic surfactant, and water as solvent.
[0032] The electrolyte solution was prepared as follows: 0.58 g ZnSO4·7H2O was weighed, 1 mL deionized water was added, stirred to fully dissolve, and nitrogen was introduced to deoxygenate for 30 min. 0.1 mg sodium dodecyl sulfate was added to the prepared zinc salt electrolyte, stirred to fully dissolve, and nitrogen was introduced to deoxygenate for 30 min.
[0033] Using the prepared zinc salt electrolyte and zinc sheets as electrodes, a traditional zinc symmetrical battery was assembled and tested. -2 At a current density of 1 mAh cm -2 At a cycle depth of Figure 3 a, lifespan is about 500h ( Figure 4 a).
[0034] Example 2
[0035] The electrolyte comprises: ZnSO4 as electrolyte, sodium dodecylbenzene sulfonate as additive anionic surfactant, and water as solvent.
[0036] The electrolyte was prepared as follows: 0.58 g ZnSO4·7H2O was weighed, 1 mL deionized water was added, stirred to fully dissolve, and nitrogen was introduced to deoxygenate for 30 min. 0.1 mg sodium dodecylbenzene sulfonate was added to the prepared zinc salt electrolyte, stirred to fully dissolve, and nitrogen was introduced to deoxygenate for 30 min.
[0037] Using the prepared zinc salt electrolyte and zinc sheets as electrodes, a traditional zinc symmetrical battery was assembled and tested. -2 At a current density of 1 mAh cm -2 At a cycle depth of Figure 3 b, lifespan is about 300h ( Figure 4 b).
[0038] Example 3
[0039] The electrolyte comprises: ZnSO4 as electrolyte, sodium dodecyl sulfate as additive anionic surfactant, and water as solvent.
[0040] The electrolyte was prepared as follows: 0.58 g ZnSO4·7H2O was weighed, 1 mL deionized water was added, stirred to fully dissolve, and nitrogen was introduced to deoxygenate for 30 min. 0.1 mg sodium dodecyl sulfate was added to the prepared zinc salt electrolyte, stirred to fully dissolve, and nitrogen was introduced to deoxygenate for 30 min. Using the prepared zinc salt electrolyte, zinc sheets were used as electrodes to assemble a traditional zinc symmetric battery and test it. At 2 mA cm -2 At a current density of 1 mAh cm -2 At a cycle depth of Figure 3 c, lifespan is about 400h ( Figure 4 c).
[0041] Example 4
[0042] The electrolyte comprises: ZnCl2 as electrolyte, sodium dodecyl sulfate as additive anionic surfactant, and water as solvent.
[0043] The electrolyte was prepared as follows: 0.27 g ZnCl2 was weighed, 1 mL deionized water was added, stirred to fully dissolve, and nitrogen was introduced to deoxygenate for 30 min. 0.1 mg sodium dodecyl sulfate was added to the prepared zinc salt electrolyte, stirred to fully dissolve, and nitrogen was introduced to deoxygenate for 30 min. Using the prepared zinc salt electrolyte, zinc sheets were used as electrodes to assemble a traditional zinc symmetrical battery and test it. At 2 mA cm -2 At a current density of 1 mAh cm -2 At a cycle depth of Figure 3 d, lifespan is about 400h ( Figure 4 d).
[0044] Example 5
[0045] The electrolyte comprises: ZnCl2 as electrolyte, sodium dodecylbenzene sulfonate as additive anionic surfactant, and water as solvent.
[0046] The electrolyte was prepared as follows: 0.27 g ZnCl2 was weighed, 1 mL deionized water was added, stirred to fully dissolve, and nitrogen was introduced to deoxygenate for 30 min. 0.1 mg sodium dodecylbenzene sulfonate was added to the prepared zinc salt electrolyte, stirred to fully dissolve, and nitrogen was introduced to deoxygenate for 30 min. Using the prepared zinc salt electrolyte, zinc sheets were used as electrodes to assemble a traditional zinc symmetrical battery and test it. At 2 mA cm -2 At a current density of 1 mAh cm -2 At a cycle depth of Figure 3 e, lifespan is about 500h ( Figure 4 e).
[0047] Example 6
[0048] The electrolyte comprises: ZnCl2 as electrolyte, sodium dodecyl sulfate as additive anionic surfactant, and water as solvent.
[0049] The electrolyte was prepared as follows: 0.27 g ZnCl2 was weighed, 1 mL deionized water was added, stirred to fully dissolve, and nitrogen was introduced to deoxygenate for 30 min. 0.1 mg sodium dodecyl sulfate was added to the prepared zinc salt electrolyte, stirred to fully dissolve, and nitrogen was introduced to deoxygenate for 30 min. Using the prepared zinc salt electrolyte, zinc sheets were used as electrodes to assemble a traditional zinc symmetrical battery and test it. At 2 mA cm -2At a current density of 1 mAh cm -2 At a cycle depth of Figure 3 f, lifespan is about 500h ( Figure 4 f).
[0050] Comparative Example 1
[0051] After replacing the surfactant with a cationic surfactant, the deposition morphology and cycle performance were poor.
[0052] The electrolyte comprises: ZnSO4 as electrolyte, hexadecyltrimethylammonium bromide as additive cationic surfactant, and water as solvent.
[0053] The electrolyte was prepared as follows: 0.58 g ZnSO4·7H2O was weighed, 1 mL deionized water was added, stirred to fully dissolve, and nitrogen was introduced to deoxygenate for 30 min. 0.1 mg hexadecyltrimethylammonium bromide was added to the prepared zinc salt electrolyte, stirred to fully dissolve, and nitrogen was introduced to deoxygenate for 30 min. Using the prepared zinc salt electrolyte, zinc sheets were used as electrodes to assemble a traditional zinc symmetrical battery and test it. At 2 mA cm -2 At a current density of 1 mAh cm -2 At a cycle depth of Figure 5 a, lifespan is about 50h ( Figure 5 b).
[0054] Comparative Example 2
[0055] After replacing the surfactant with a non-ionic surfactant, the deposition morphology and cycle performance were poor.
[0056] The electrolyte comprises: ZnSO4 as electrolyte, polysorbate as additive non-ionic surfactant, and water as solvent.
[0057] The electrolyte was prepared as follows: 0.58 g ZnSO4·7H2O was weighed, 1 mL deionized water was added, stirred to fully dissolve, and nitrogen was introduced to deoxygenate for 30 min. 0.1 mg polysorbate was added to the prepared zinc salt electrolyte, stirred to fully dissolve, and nitrogen was introduced to deoxygenate for 30 min. Using the prepared zinc salt electrolyte, zinc sheets were used as electrodes to assemble a traditional zinc symmetrical battery and test it. At 2 mA cm -2 At a current density of 1 mAh cm -2 At a cycle depth of Figure 6 a, lifespan is about 60h ( Figure 6 b).
Claims
1. A novel electrolyte for a near-neutral zinc ion battery, characterized in that The electrolyte is mainly composed of zinc salt electrolyte; the additive is an amphiphilic anionic surfactant, which includes a strong hydrophobic group and an ionic group.
2. The novel nearly neutral zinc ion battery electrolyte according to claim 1, characterized in that: The zinc salt electrolyte includes one or more of zinc sulfate, zinc chloride, zinc acetate, zinc nitrate, zinc perchlorate, and zinc tetrafluoroborate; The zinc salt electrolyte concentration is 0.2M-3M.
3. The novel nearly neutral zinc ion battery electrolyte according to claim 1, characterized in that: The anionic surfactants include alkyl sulfates, alkyl sulfonates, and alkylbenzene sulfonates.
4. The novel nearly neutral zinc ion battery electrolyte according to claim 3, characterized in that: The alkyl group in the alkyl sulfate, alkyl sulfonate and alkyl benzene sulfonate is a straight chain or branched chain alkyl group with a carbon number of 6 to 18.
5. The novel nearly neutral zinc ion battery electrolyte according to claim 1, characterized in that: The concentration of the anionic surfactant is 0.01 g L -1 -10g L -1 .
6. A method for preparing a novel near-neutral zinc ion battery electrolyte according to any one of claims 1 to 5, the method comprising the following steps: (1) weighing zinc salt powder by mass, adding deionized water, stirring and dissolving, and obtaining a zinc salt electrolyte solution; (2) introducing nitrogen into the zinc salt electrolyte solution obtained in step (1) and ultrasonicating it for 30 minutes to uniformly disperse it and remove dissolved oxygen in the electrolyte solution; (3) weighing an amphiphilic anionic surfactant additive in proportion, and adding the additive to the zinc salt electrolyte solution obtained in step (2) to obtain a zinc salt electrolyte solution containing an amphiphilic anionic surfactant; (4) nitrogen is introduced into the zinc salt electrolyte solution containing an anionic surfactant having amphiphilicity obtained in step (3) and ultrasonicated for 30 minutes to uniformly disperse the solution and remove dissolved oxygen in the electrolyte solution, thereby obtaining a novel electrolyte containing anionic surfactant for zinc ion batteries.
7. A novel zinc ion battery, characterized in that: The electrolyte comprises the electrolyte described in any one of claims 1 to 5, wherein the negative electrode side is metallic zinc, and the positive electrode side is vanadium-based oxides, manganese-based oxides, Prussian blue analogs, and organic compounds such as polyaniline.
8. The battery according to claim 7, characterized in that: The zinc on the negative electrode side is one of zinc sheet, zinc powder, foamed zinc and zinc-copper alloy.
9. The battery according to claim 7, characterized in that: The vanadium-based oxide on the positive electrode side includes one or more of vanadium trioxide, vanadium pentoxide, vanadium trioxide octaoxide, vanadium dioxide and corresponding ion intercalation compounds thereof.
10. The battery according to claim 7, characterized in that: The manganese-based oxide on the positive electrode side includes one or more of α, β, δ, and γ-MnO2 compounds.
Citation Information
Patent Citations
Aqueous zinc ion battery electrolyte and battery
CN113782842A
Preparation method and application of non-ionic surface active agent modified zinc ion battery electrolyte
CN116454279A